2016
DOI: 10.1016/j.molmet.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

White-to-brite conversion in human adipocytes promotes metabolic reprogramming towards fatty acid anabolic and catabolic pathways

Abstract: ObjectiveFat depots with thermogenic activity have been identified in humans. In mice, the appearance of thermogenic adipocytes within white adipose depots (so-called brown-in-white i.e., brite or beige adipocytes) protects from obesity and insulin resistance. Brite adipocytes may originate from direct conversion of white adipocytes. The purpose of this work was to characterize the metabolism of human brite adipocytes.MethodsHuman multipotent adipose-derived stem cells were differentiated into white adipocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 69 publications
7
116
3
Order By: Relevance
“…We observed that chronic CA treatment upregulates the expression of lipolytic genes ( Hsl, Atgl), key regulators in fatty acid oxidation ( Cpt1b, Ppara ), lipogenic genes ( Gyk, Dgat1 ) , and Pdk4 , an enzyme that enhances lipid metabolism and has recently been reported to be responsible for major metabolic adaptations during white-to-beige conversion of human adipocytes (Fig. 2J, L, and M) [13]. Increased oxidative metabolism in mitochondria is known to be accompanied by increased reactive oxygen species (ROS) production.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that chronic CA treatment upregulates the expression of lipolytic genes ( Hsl, Atgl), key regulators in fatty acid oxidation ( Cpt1b, Ppara ), lipogenic genes ( Gyk, Dgat1 ) , and Pdk4 , an enzyme that enhances lipid metabolism and has recently been reported to be responsible for major metabolic adaptations during white-to-beige conversion of human adipocytes (Fig. 2J, L, and M) [13]. Increased oxidative metabolism in mitochondria is known to be accompanied by increased reactive oxygen species (ROS) production.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, cold exposure increases expression of genes responsible for replenishing lipid droplets in BAT, including the genes that mediate glucose uptake, lipogenesis, and TAG synthesis ( Glut1 , Glut4 , hexokinase , PFK1 , PDHa1 , FAS , glycerol kinase, PEPCK , GPAT3 , Dgat1 , Dgat2 ) (166). PPARα or PPARγ agonists, which promote differentiation of human mesenchymal stem cells into brown/beige adipocytes, also stimulate expression of genes responsible for lipolysis, de novo lipogenesis, TAG synthesis, and lipid droplet formation (16). Therefore, lipid droplet dynamics, including lipid droplet lipolysis and replenishment, are likely to play an important role in regulating BAT and beige fat thermogenesis.…”
Section: Brown and Beige Fat Thermogensismentioning
confidence: 99%
“…Interestingly, PPARγ agonists potently increase de novo beige adipogenesis and white-to-beige adipocyte transdifferentiation in both rodents and humans (16, 188, 229, 239). The ability of PPARγ to stimulate preadipocyte differentiation into either white or brown/beige adipocytes appears to be determined by its associated coactivators.…”
Section: Genetic and Epigenetic Regulation Of Brown And Beige Fat Thementioning
confidence: 99%
“…The action of browning WAT into BAT-like adipocytes, or beige (“brite”) cells, has been further postulated to protect against obesity via body fat reduction and related complications [3235, 31, 36, 37]. Similar to BAT adipocytes, beige adipocytes have the ability to take on a BAT-like thermogenic phenotype in response to various stimuli such as cold, endocrine factors or chemical compounds.…”
Section: Bat Activation Vs Bat Inductionmentioning
confidence: 99%